Unmasking Plummer–Vinson Syndrome: A Rare Case Report - B. Radhika; Aswini Sekar; Priyanka Gandhi (Contemporary Clinical Dentistry)
This article highlights a unique case of Plummer–Vinson syndrome (PVS), also known as Paterson Brown-Kelly Syndrome. PVS is associated with a triad of symptoms, including microcytic hypochromic anemia, esophageal strictures, and dysphagia. It is commonly found in middle-aged women, particularly in the fourth and fifth decades of life, and is rarely reported in males. We present the case of a 49-year-old female patient who exhibited the classic symptoms of PVS. Given that PVS is a precancerous condition with a high potential for malignancy, early diagnosis is crucial for a better prognosis. Surveillance endoscopy and barium swallow test are recommended for monitoring. Iron repletion often improves dysphagia, and in some cases, esophageal dilatation is used to provide symptomatic relief. The mutual interaction of systemic and oral health is often underestimated, especially by patients in developing countries. Therefore, this report emphasizes the importance of thorough medical history taking and its relevance to dental health and treatment.